Uncovering the latent potential of (re)appropriated neglected spaces: The transformation of Melgisedek towards addressing issues of homelessness and heritage - Swart, Johan (University of Pretoria, 2022)
Mini Dissertation (MArch(Prof))--University of Pretoria, 2021.